Analisis Kemampuan Numerasi Siswa Kelas V SDS Dharma Bakti - Ika Apriliana Putri; Syifa Kirani Putri; Qutrunnada Salsabila Yusup (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research aims to evaluate the numeracy skills of fifth-grade students at Dharma Bakti Private Elementary School by comparing their performance on pre-tests and post-tests. Utilizing a descriptive qualitative approach, the study focused on a group of 26 fifth-grade students. Data was gathered through a series of pre-tests and post-tests, each containing 20 questions that assessed the students' numerical competencies. The analysis revealed the numeracy levels of these students, with the average pre-test score being 27. This score reflects the students' initial understanding of numerical concepts and skills. The post-test results showed a slight increase, with an average score of 28. These findings indicate that the numeracy skills of the students at Dharma Bakti Private Elementary School are relatively low, highlighting the need for enhanced support from both teachers and students to improve these skills.